Probing different perfluorocarbons for in vivo inflammation imaging by 19F MRI: image reconstruction, biological half‐lives and sensitivity. (19th December 2013) - Jacoby, Christoph; Temme, Sebastian; Mayenfels, Friederike; Benoit, Nicole; Krafft, Marie Pierre; Schubert, Rolf; Schrader, Jürgen; Flögel, Ulrich
<x xml:space="preserve">Abstract</x> Inflammatory processes can reliably be assessed by 19F MRI using perfluorocarbons (PFCs), which is primarily based on the efficient uptake of emulsified PFCs by circulating cells of the monocyte–macrophage system and subsequent infiltration of the 19F‐labeled cells into affected tissue. An ideal candidate for the sensitive detection of fluorine‐loaded cells is the biochemically inert perfluoro‐15‐crown‐5 ether (PFCE), as it contains 20 magnetically equivalent 19F atoms. However, the biological half‐life of PFCE in the liver and spleen is extremely long, and so this substance is not suitable for future clinical applications. In the present study, we investigated alternative, nontoxic PFCs with predicted short biological half‐lives and high fluorine content: perfluorooctyl bromide (PFOB), perfluorodecalin (PFD) and trans‐bis‐perfluorobutyl ethylene (F‐44E). Despite the complex spectra of these compounds, we obtained artifact‐free images using sine‐squared acquisition‐weighted three‐dimensional chemical shift imaging and dedicated reconstruction accomplished with in‐house‐developed software. The signal‐to‐noise ratio of the images was maximized using a Nutall window with only moderate localization error. Using this approach, the retention times of the different PFCs in murine liver and spleen were determined at 9.4 T. The biological half‐lives were estimated to be 9 days (PFD), 12 days (PFOB) and 28 days (F‐44E), compared with more than 250 days for PFCE. In vivo sensitivity for inflammation imaging was assessed using an ear clip injury model. The alternative PFCs PFOB and F‐44E provided 37% and 43%, respectively, of the PFCE intensities, whereas PFD did not show any signal in the ear model. Thus, for in vivo monitoring of inflammatory processes, PFOB emerges as the most promising candidate for possible future translation of 19F MR inflammation imaging to human applications. Copyright © 2013 John Wiley & Sons, Ltd.